2000
DOI: 10.1046/j.1523-1755.2000.00336.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bicarbonate- and lactate-buffered replacement fluids on cardiovascular outcome in CVVH patients

Abstract: The results show that the administration of RF-bic solution was superior in normalizing acidosis of patients without the risk of alkalosis. The data also suggest that the use of RF-bic during CVVH reduces cardiovascular events in critically ill patients with acute renal failure, particularly those with previous cardiovascular disease or heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(63 citation statements)
references
References 22 publications
3
58
0
2
Order By: Relevance
“…[96][97][98] Lactate is noted to rise during lactate-based RRT and may have deleterious cardiovascular side effects and is associated with poor outcomes. 95,96,[98][99][100][101] It is unclear whether lactate induces injury or is simply a marker of dysoxia and abnormal liver metabolism of lactate during critical illness hence its association with mortality. Although some fluids still contain minimal lactate (~3 mEq), most fluids are bicarbonate (20-24 mEq/L) based.…”
Section: Dosementioning
confidence: 99%
“…[96][97][98] Lactate is noted to rise during lactate-based RRT and may have deleterious cardiovascular side effects and is associated with poor outcomes. 95,96,[98][99][100][101] It is unclear whether lactate induces injury or is simply a marker of dysoxia and abnormal liver metabolism of lactate during critical illness hence its association with mortality. Although some fluids still contain minimal lactate (~3 mEq), most fluids are bicarbonate (20-24 mEq/L) based.…”
Section: Dosementioning
confidence: 99%
“…[7] This led to the assumption that exogenous lactate may be harmful and promoted the use of bicarbonate-buffered solutions. [4,8,9] The exogenous lactate load should be avoided in patients with lactic acidosis for two reasons: the decreased ability of the body to use lactate, and the better hemodynamic stability with bicarbonate. [4,10] We demonstrated that blood lactate and glucose levels were higher and bicarbonate and insulin requirements were higher in the PD group than that in the bic-HS group.…”
Section: Discussionmentioning
confidence: 99%
“…[4,8,9] The exogenous lactate load should be avoided in patients with lactic acidosis for two reasons: the decreased ability of the body to use lactate, and the better hemodynamic stability with bicarbonate. [4,10] We demonstrated that blood lactate and glucose levels were higher and bicarbonate and insulin requirements were higher in the PD group than that in the bic-HS group. Zimmerman et al [11] demonstrated that both lactate and bicarbonate-based solutions result in the same degree of effective clearance, but that plasma lactate levels are higher in patients on lactate-based dialysis solutions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations